Forecasting the Number of Visitors of the Museums and Ruins by Using Time Series Analysis: The Case of Turkey - Mustafa Agah Tekindal; Semanur Öztemiz (Türk Kütüphaneciliği)
Objectives: As cultural places, museums and ruins are inseparable parts of the creation process of cultural and historical identity. The cultural heritage products covered by museums and ruins can be thought as a representation of a community and its highest values and truths. It is precisely for these reasons that the interest shown to museums and ruins can give clue for future plans of the cultural institutions in a country. The aim of this research is to forecast the number of visitors to the museums and ruins until 2037 in Turkey. Method: The research material consists of data about the number of visitors of the museums and ruins, between 2001 and 2019 in Turkey. The data were obtained from the Turkish Statistical Institute (TÜİK). Research data was analysed under the framework of Auto Regressive Integrated Moving Average (ARIMA) time series analysis in order to predict the future numbers of visitors to museums and ruins. Findings: The research findings show that time series contain highly usable estimates which indicate an increasing trend for the number of visitors to the museums and ruins in Turkey. Originality: The findings can also allow comparative studies, in which the issues about physical and digital users are compared, for museums and ruins which are willing to convert their content to digital platforms. Results: In addition to practical implications, the present study is expected to contribute to the literature.